Crecimiento inicial de tres especies forestales establecidas en un ensayo de restauración ecológica en el matorral andino del Parque Universitario “Francisco Vivar Castro”, cantón y provincia de Loja - Pacheco Cueva, Ivett Carolina (2024)
The Andean scrubland is an ecosystem that harbors a high diversity of native vegetation, despite its biological importance, it has suffered constant alterations due to fires, species exploitation, planting of exotic species and expansion of the agricultural frontier, which has caused its degradation. The objective of this study was to evaluate the survival and increase in diameter and height, and to analyze the edaphic factors of the site that are related to the development of the three forest species in the first phase of the ecological restoration trial. Three native species were planted: Lafoensia acuminata, Podocarpus sprucei and Handroanthus chrysanthus in uniform plots, with a distance of 3 x 3 m between each individual and 60 individuals per species in each trial. Basal diameter and height of the species and soil characteristics were measured: texture, slope, bulk density, pH, organic matter and carbon, and the phytosanitary status of the plants, at the beginning of the trial and after 11 months of monitoring. Survival, increases in basal diameter, total height, and the relationship of growth with soil variables were calculated. High survival of Lafoensia acuminata (100 %), Handroanthus chrysanthus (≥ 93 %) and Podocarpus sprucei (≥ 85 %) was observed. Basal diameter, in trial I, was greater than 0.17 cm in Handroanthus chrysanthus, followed by Podocarpus sprucei with 0.14 cm and Lafoensia acuminata with 0.12 cm. In trial II, Handroanthus chrysanthus showed the highest growth with 0.12 cm, followed by Podocarpus sprucei with 0.10 cm and Lafoensia acuminata with 0.09 cm. In terms of height, Lafoensia acuminata recorded the highest growth in both trials, with 5.55 cm in trial I and 2.93 cm in trial II, followed by Podocarpus sprucei and Handroanthus chrysanthus. There were significant differences (< 0.0001) in the increase in basal diameter and total height between Lafoensia acuminata and Handroanthus crhysanthus. The edaphic variables related to initial growth were pH, bulk density, organic matter and carbon. Preliminarily, it is concluded that the three species show potential for reforestation of this Andean shrubland; Lafoensia acuminata was the one with the best initial survival and growth.